The Infection Control Paradox: Exploring Knowledge and Practices of ICU Nurses Across Hospitals in Punjab, Pakistan - Sattar, Amina; Tehreem, .; Yaseen, Sania; Batool, Fatima; Danish, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Hospital-acquired infections (HAIs) continue to pose a serious challenge to patient safety, particularly in intensive care units (ICUs) where patients are most susceptible. Nurses are central to infection prevention and control (IPC), yet a persistent gap between knowledge and practice undermines infection control efforts, especially in resource-constrained healthcare settings such as Pakistan. Objective: This study aimed to evaluate ICU nurses' knowledge and self-reported practices regarding IPC measures and to determine the relationship between these two domains in tertiary care hospitals across Punjab, Pakistan. Methods: A descriptive cross-sectional study was conducted among 150 ICU nurses working in selected public and private tertiary hospitals. Data were gathered using a pre-validated structured questionnaire developed in accordance with World Health Organization (WHO) and Centers for Disease Control and Prevention (CDC) guidelines. Knowledge and practice levels were categorized as good (≥75%), moderate (50-74%), or poor (<50%). Data were analyzed using SPSS version 26, applying descriptive statistics, chi-square tests, and Pearson's correlation analysis. Results: The findings indicated moderate levels of knowledge (mean = 11.2 ± 2.1) and practice (mean = 10.6 ± 2.4) among the participants. Only 36% demonstrated good knowledge, while 32.7% exhibited good practices. Notable gaps were found in hand hygiene duration, sterilization techniques, needlestick injury management, and consistent use of N95 masks. Nurses with higher educational qualifications showed significantly better knowledge (p = 0.02), and those with greater years of experience demonstrated better practices (p = 0.01). A strong positive correlation was identified between knowledge and practice scores (r = 0.62, p < 0.001). Conclusion: ICU nurses in Punjab displayed moderate knowledge of IPC but suboptimal implementation in clinical practice. The observed knowledge-practice gap highlights the influence of both personal and institutional factors. Strengthening regular IPC training programs, ensuring continuous supervision, and enhancing resource availability are critical for fostering a robust infection control culture and reducing the burden of HAIs in ICUs.